Chain initiation factor 3 crosslinks to E. coli 30S and 50S ribosomal subunits and alters the UV absorbance spectrum of 70S ribosomes. - Chaires, J B (1982)
We report a direct procedure to determine the proteins near the IF-3 binding site in purified 30S and 50S ribosomal subunits. This procedure introduces only limited numbers of cleavable crosslinks between IF-3 and its nearest neighbors. The cleavable crosslinking reagent, 2-iminothiolane, was used to crosslink IF-3 in place to both 30S and 50S subunits. Ribosomal proteins S9/S11, S12, L2, L5 and L17 were found, by this approach, to be in close proximity to the factor in purified IF-3-subunit complexes. In addition, IF-3 was shown to alter the ultraviolet absorbance spectrum of E. coli 70S ribosomes at 10 mM Mg2+. The magnitude of the observed difference spectrum at a constant IF-3/ribosome ratio of 1.0, is linearly dependent upon ribosome concentration over the range 5 nM - 55 nM. Titration experiments indicated that the observed effect is maximal at an IF-3/ribosome ratio of approximately 1.0. These results are taken to indicate a conformational change in the 70S ribosome induced by IF-3.